2005
DOI: 10.1038/sj.bjc.6602453
|View full text |Cite|
|
Sign up to set email alerts
|

Dexamethasone-induced cisplatin and gemcitabine resistance in lung carcinoma samples treated ex vivo

Abstract: Chemotherapy for lung cancer not only has severe side effects but frequently also exhibits limited, if any clinical effectiveness. Dexamethasone (DEX) and similar glucocorticoids (GCs) such as prednisone are often used in the clinical setting, for example, as cotreatment to prevent nausea and other symptoms. Clinical trials evaluating the impact of GCs on tumour control and patient survival of lung carcinoma have never been performed. Therefore, we isolated cancer cells from resected lung tumour specimens and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…So these findings are partially in contrast to those reported by Zhang et al (19) who demonstrated glucocorticoid-induced resistance to chemotherapy in the majority of cell lines derived from various malignancies including brain, breast, cervix, melanoma and neuroblastoma. Gassler et al (14) found an anti-apoptotic effect of glucocorticoids in tissue samples from lung cancer. Glucocorticoids are also highly likely to induce resistance and accelerated tumor growth in patients with prostate, renal cell, bladder and testicular cancer (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So these findings are partially in contrast to those reported by Zhang et al (19) who demonstrated glucocorticoid-induced resistance to chemotherapy in the majority of cell lines derived from various malignancies including brain, breast, cervix, melanoma and neuroblastoma. Gassler et al (14) found an anti-apoptotic effect of glucocorticoids in tissue samples from lung cancer. Glucocorticoids are also highly likely to induce resistance and accelerated tumor growth in patients with prostate, renal cell, bladder and testicular cancer (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past few years several publications have discussed the potential of glucocorticoids like dexamethasone to induce resistance to antineoplastic agents (14,15). Thus, the question arises if dexamethasone used to prevent or treat allergic reactions to cetuximab may also lead to resistance to the agent in the treatment of SCCHN.…”
Section: A B Cmentioning
confidence: 99%
“…Recently, more and more data from preclinical studies, and to some extent from clinical studies, have strongly recommended a GC-conferred resistance to cancer therapy in the majority of malignant solid tumors -irrespective of tumor origin and the nature of specific anticancer drugs (Wolff et al 1996, Weller et al 1997, Webster et al 2002, Herr et al 2003, Wu et al 2004, Gassler et al 2005, Runnebaum & Brüning 2005, Sui et al 2006, Zhang et al 2006a,b,c,d,e, 2007. In this study, we have demonstrated that Dex could protect human ovarian IgG (10 µg/ml) Anti-β1 (µg/ml) Figure 4 Dex-enhanced cell attachment and cell survival are partially reversed by integrin b1-blocking antibody.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data indicate that GCs can inhibit apoptosis induced by chemotherapy not only in established cancer cell lines and tumor xenografts, but also in the freshly isolated cells from surgical resections from tumors of various origins, including ovary, breast, prostate, pancreas, liver, colon, brain, cervix, bone, skin, and nervous system (Herr et al 2003, Sui et al 2006, Zhang et al 2006a. In addition, the anti-chemotherapeutic effect of GCs can be seen in several anticancer drugs including cisplatin (Wolff et al 1996, Gassler et al 2005, Zhang et al 2006a,b,d, 2007, paclitaxel (Wu et al 2004, Sui et al 2006, 5-fluorouracil (Zhang et al 2006a(Zhang et al , 2007, adriamycin (Weller et al 1997), actinomycin D (Wolff et al 1996), doxorubicin (Wu et al 2004), and gemcitabine (Gassler et al 2005, Zhang et al 2007). The GC-induced pro-survival effects should be of important clinical relevance when they interfere with the effect of chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…After treatment, the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay was performed as recently described. 27 Migration to chemoattractants measured by transwell chamber migration assay A ChemoTx System (Neuro Probe Inc., Gaithersburg, MD, USA) with 96 wells was used for the migration assay. The polycarbonate membrane pore size of 12 mm was selected to allow passage of mammalian cells.…”
Section: Evaluation Of Msc Differentiationmentioning
confidence: 99%